Strategi Pemilihan Pesawat Angkut Militer Produksi PT. Dirgantara Indonesia Untuk Mendukung Industri Pertahanan Dalam Negeri - Joan Ferdiyanto; I Made Wira Hadi Arsanta; Sadimin Sadimin (Universitas Trunojoyo Madura, 2022)
Indonesian Navy flights as an integral part of the SSAT have several functions, one of which is to provide rapid logistical support. Based on considerations of function and mobilization capabilities, medium-sized military transport aircraft are the main choice in providing rapid logistical support. The advantages of this function and mobility also make military transport aircraft capable of carrying out additional tasks assigned to their guiding squadron, namely the 600 Air Wing Squadron. The additional tasks are Search and Rescue (SAR), Air Medical Evacuation (EMU) and VIP Flights. Currently, there are 11 elements of the NC212-200 aircraft owned by Puspenerbal, with a description of 7 active elements, 4 disposal processes. In 2017, Puspenerbal received the Beechcraft King Air 350i light transport aircraft, but several operational requirements were not met to carry out the main function as an element of fast logistics support provider, so this element was prioritized to carry out additional functions such as VIP flights. The results of the analysis using the Analytic Hierarchy Process (AHP) method with the help of the Expert Choice 11 Application show the weight of the criteria for selecting medium military transport aircraft, namely Navigation and Communication Equipment 46.4%, Short Take-off and Landing (STOL) Ability 31.7 %, Transportability 15.3%, and Flying Ability 6.7% with an Inconsistency value of 0.07. This shows that the calculation of the correspondent is still within the inconsistency threshold, which cannot be more than 0.1. While the order of priority for the alternative types of medium military transport aircraft from high to low is the CN 295 type 80.5% and the Alenia C27J Spartan type 19.5%. Based on this value, it can be seen that the CN 295 Medium Military Transport Aircraft is the right alternative to be chosen.